Is the Goat a New Host for the G3 Indian Buffalo Strain of Echinococcus granulosus?. (15th May 2012) - Calderini, Pietro; Gabrielli, Simona; Cancrini, Gabriella
Abstract : Four goats bred in Central Italy (province of Rieti) revealed, in the liver, metacestodes of Echinococcus granulosus . The cysts, unilocular and fertile, were examined by microscopy and molecular diagnostics. Morphological data on the rostellar hooks are in agreement with the original description of the strain found in buffaloes and are largely compatible with those reported in Europe for cattle and humans. Specific PCR followed by DNA sequencing of the mitochondrial cox1 gene revealed for all the isolates 99.5% identity to the reference strain G3 genotype and 99.3% and 99.1% to G2 and G1, respectively. Further genetic markers (nad1 and 12S rRNA) confirmed the identity of the goat isolates to the G3 strain. This genotype, here reported for the first time in goats, proved to have a wider than previously supposed host range, therefore its relevance in human hydatidosis is expected to be more often evidenced.